The impact of the new international land-sea trade corridor on trade between China and ASEAN - Li, Yi; Abd Rahman, Muhammad Daaniyall; Utit, Chakrin (Cogent OA, 2025)
The construction of new international land and sea trade corridors (ILSTC) has improved transportation infrastructure along the routes and facilitated improved trade mechanisms. Based on data from 13 Chinese provinces and ASEAN from 2012-2021, this article applies an extended gravity model to explore the following questions: (1) Does the ASEAN countries’ participation in the construction of the ILSTC promote their trade growth with China; (2) Whether the construction of the ILSTC improves the railroads, highways, and waterway transportation infrastructure of the 13 Chinese provinces facilitated trade growth with ASEAN countries? The study found that: first, ASEAN countries’ participation in ILSTC construction significantly impacted their trade growth with China. Second, the ILSTC improves railroad and highway transportation facilities in 13 Chinese provinces and significantly contributes to their trade growth with ASEAN countries. However, its trade effect on waterway transport is not significant, primarily due to insufficient investment in the development of inland waterway infrastructure in 13 provinces of China and the limitations posed by natural conditions. Based on the findings, this study recommends strengthening policy coordination, advancing infrastructure and digital-intelligent development, promoting trade facilitation and liberalization, and fostering industrial integration. This provides a reference value for further participation in the ILSTC.